(untitled) (Somma: Revista Científica do Instituto Federal do Piauí, 2026)
Introduction. Pratylenchus coffeae occurs in yam (Dioscorea spp.) production areas, reducing tuber yield and quality. Objective. To evaluate the host suitability of forage sorghum ‘BRS Ponta Negra’ to P. coffeae and the nematicidal activity of aqueous extracts from Croton sp., Monteverdia rigida, Sarcomphalus joazeiro, Sideroxylon obtusifolium, Byrsonima gardneriana, Astronium urundeuva, and Tocoyena formosa against this nematode. Material and Methods. In two greenhouse experiments, 37-day-old sorghum plants were inoculated with 250, 500, 750, or 1,000 nematodes (juveniles and adults). Yam plants were used as a susceptible control. Eighty days after inoculation, the number of nematodes in roots and soil, as well as the reproduction factor (RF), were evaluated. Aqueous plant extract concentrations (0% - control; 0.5%; 1.0%; 1.5%; and 2.0%) were tested by adding 200 μL of each extract and 25 nematodes per cavity in Kline plates. After 24 h, immobile specimens were counted and transferred to distilled water for an additional 24 h to determine mortality. Results and Discussion. Forage sorghum ‘BRS Ponta Negra’ was classified as a poor host for P. coffeae (0 ≤ RF < 1). All plant extracts caused immobility and mortality in P. coffeae, with the leaf extract of S. obtusifolium being the most effective, resulting in mortality rates above 90% at all concentrations tested. Conclusion. ‘BRS Ponta Negra’ shows potential for use in crop rotation systems. The leaf extract of S. obtusifolium demonstrates high nematicidal activity against P. coffeae.